2017
DOI: 10.1016/j.jad.2017.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Severity of anxiety– but not depression– is associated with oxidative stress in Major Depressive Disorder

Abstract: Background Oxidative stress is implicated in both depression and anxiety, but it is currently unclear whether this relates to syndromal diagnoses or trans-diagnostic dimensional symptoms. We examined the relationship between oxidative stress and severity of depression and anxiety symptoms in individuals with Major Depressive Disorder (MDD). Methods Plasma oxidative stress markers F2-isoprostanes and oxidized glutathione (GSSG), and the antioxidant reduced glutathione (GSH), were assessed in 69 physically hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 84 publications
2
33
1
Order By: Relevance
“…Findings from studies that measured ROS metabolites or markers of oxidative damage are largely unanimous in reporting increased oxidative stress in highly anxious individuals [43], particularly when inflammation and activation of the hypothalamic-pituitary-adrenal (HPA) axis and sympathetic nervous system are involved [44]. Thus, in humans, different markers of lipid peroxidation, such as malondialdehyde (MDA) [45] and F2-isoprostanes [46] have been reported to be increased in blood samples from high anxiety patients. Similarly, in rodents, natural and genetically-selected variation in basal anxiety has been consistently associated with markers of oxidative damage in both neurons and glia in several brain regions (e.g., cerebellum, hippocampus, cortex, nucleus accumbens) and in peripheral blood cells [36,47,48].…”
Section: Findings On Measurements Of Oxidative Stressmentioning
confidence: 99%
“…Findings from studies that measured ROS metabolites or markers of oxidative damage are largely unanimous in reporting increased oxidative stress in highly anxious individuals [43], particularly when inflammation and activation of the hypothalamic-pituitary-adrenal (HPA) axis and sympathetic nervous system are involved [44]. Thus, in humans, different markers of lipid peroxidation, such as malondialdehyde (MDA) [45] and F2-isoprostanes [46] have been reported to be increased in blood samples from high anxiety patients. Similarly, in rodents, natural and genetically-selected variation in basal anxiety has been consistently associated with markers of oxidative damage in both neurons and glia in several brain regions (e.g., cerebellum, hippocampus, cortex, nucleus accumbens) and in peripheral blood cells [36,47,48].…”
Section: Findings On Measurements Of Oxidative Stressmentioning
confidence: 99%
“…A meta-analysis of 18 studies found that oxidative stress is increased in adults with depression, although larger-scale studies are needed [52]. There also is evidence for elevated oxidative stress in adults with anxiety symptomatology [53], Attention Deficit Hyperactivity Disorder (ADHD) [54], and schizophrenia [55].…”
Section: Introductionmentioning
confidence: 99%
“…Ovariectomy causes oxidative stress in different central nervous system structures owing to depletion of antioxidant content leading to an anxiogenic profile (Da Silva Morrone et al, 2016). In human populations, anxiolytic effect of dietary antioxidants (Boldrini et al, 2018) and a positive correlation between peripheral blood oxidative stress markers and anxiety behavior (Steenkamp et al, 2017) have been reported as well. Thus, the anxiolytic effect of vitamin E in rodents and human populations may be ascribed to its antioxidant properties.…”
Section: Discussionmentioning
confidence: 98%